Romance, Recognition and Revenge in Marie Clements’s The Unnatural and Accidental Women - Bamford, Karen (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
This essay considers the relationship of Marie Clements’s The Unnatural and Accidental Women to European traditions of drama and folk narrative, and especially its relation to the genres of revenge tragedy and romance. It argues that Clements transforms and subsumes the latter in a feminist, maternal romance. In contrast to the traditional family romance, from Homer’s Odyssey to Shakespeare’s Pericles, and its folktale analogues (Cinderella and Peau d’Asne, and the related Dear as Salt), which operate to gratify paternal wishes, Clements’s romance gratifies a mother’s desire for reunion and reconciliation with her daughter. In contrast to the resolution of Renaissance revenge plots, in which the revenger typically dies to satisfy the claims of justice, here the female protagonist achieves a rebirth symbolized by the recognition she shares with her mother. Like the romance tradition which it transforms, the play offers us a vision of an ideal world, here symbolized in "the first supper" that concludes the play. Résumé Cet article s’intéresse au rapport entre la pièce The Unnatural and Accidental Women de Marie Clements et les traditions européennes du théâtre et du récit folklorique, surtout en ce qui a trait aux genres de la tragédie de vengeance et du récit romantique. L’auteure fait valoir que Clements transforme et module ce dernier genre en romance féministe et maternelle. Contrairement à la romance familiale traditionnelle, de l’Odyssée d’Homère en passant par le Périclès de Shakespeare, et des contes populaires analogues (Cendrillon. Peau d’Âne et Bien comme le sel, qui portent sur le même thème), où il faut répondre aux souhaits du père, la romance de Clements répond au désir qu’a une mère de retrouver sa fille et de se réconcilier avec elle. Contrairement à la résolution des complots de vengeance de la Renaissance, dans lesquels le vengeur meurt généralement pour satisfaire la justice, dans ce cas, la protagoniste renaît symboliquement dans la reconnaissance partagée avec sa mère. À l’instar de la tradition romantique qu’elle cherche à transformer, la pièce nous offre une vision d’un monde idéal, symbolisé par le «.premier repas.» qui lui sert de conclusion.